Calreticulin--the potential autoantigen in celiac disease - Karská, K; Tucková, L; Steiner, L; Tlaskalová-Hogenová, H; Michalak, M (Biochemical and biophysical research communications, 1995)
Monoclonal antibodies to gliadin were recently found to cross-react with epitopes on rat enterocytes. Two molecules of mol. mass 62 and 66 kDa were isolated from enterocyte lysates by affinity chromatography using antigliadin monoclonal antibodies. The N-terminal amino acid sequence of the 62-kDa protein was determined to be XXXIYFKEQFLD. This amino acid sequence corresponds to amino acid sequence of rat calreticulin. The presence of calreticulin in enterocyte lysates was further confirmed using anticalreticulin serum. Anticalreticulin serum was also used to investigate the reactivity of isolated rat calreticulin. To analyze whether gliadin and calreticulin share similar epitopes recognized by anticalreticulin antibodies, synthetic dodecapeptides derived from the amino acid sequence of alpha gliadin were used in competitive ELISA assay. Two gliadin peptides, QEQVPLVQQQQF and YQLLQELCCQHL, were found to inhibit the binding of rabbit anti-rat calreticulin sera to rat calreticulin. The significant correlation was detected between IgA anticalreticulin and antigliadin antibodies (r = 0.827; P < 0.001) in celiac patients.
Keywords: Autoantigens; sekvenční seřazení; Epitope Mapping; Calreticulin; Humans; sekvenční homologie aminokyselin; autoantigeny; Sequence Homology, Amino Acid; Molecular Sequence Data; molekulární sekvence - údaje; Calcium-Binding Proteins; Antibodies, Monoclonal; ribonukleoproteiny; krysa rodu Rattus; lidé; zvířata; Immunoglobulin A; mapování epitopu; Amino Acid Sequence; gliadin; celiakie; Gliadin; proteiny vázající vápník; Sequence Alignment; kalretikulin; monoklonální protilátky; Celiac Disease; imunoglobulin A; Rats; Animals; Ribonucleoproteins; sekvence aminokyselin